FORMATION OF MODERN SKILLS BY ORGANIZING A ROLE-PLAYING GAME IN READING LITERACY CLASSES (Web of Teachers: Inderscience Research, 2024)
This article focuses on ways to engage students in collaboration, communication, critical and creative thinking through the use of role-playing in literacy instruction.